Collaborative servitization in service-oriented company: The case study of telco company - Stosic, Biljana; Mihailovic, Jovana; Milutinovic, Radul (PloS one, 2024)
There is a growing interest in the subject of product-service system (PSS) and collaborative servitization in academia and practice. However, the focus is on exploring the growth of manufacturing companies without specifically analyzing the growth of service companies in applying PSS. There are companies, especially in the telco industry, that expand their service business to complex bundles of products and services. The paper investigates PSS in the service company and the role of collaboration in different PSS development phases: idea generation, development and go to market phase. The study adopted case-based research conducted in international Telco organization. The research demonstrates how a company creates and commercializes integrated packets of products and services, it identifies partners company works with and the benefits and challenges of their cooperation. The study addresses collaboration with customers and identifies five different customer profiles according to their openness to participate in the development of PSS. The study highlights the importance of (1) collaboration models, (2) customer involvement, and (3) strategic focus in successful application of collaborative servitization. The findings complement the literature for collaborative servitization and offer concrete input for companies in terms of how to better organize business, profit from collaboration models and gain market advantage.